Drivers for emerging issues in animal and plant health. (June 2016) - Richardson, Jane; Lockhart, Caryl; Pongolini, Stefano; Karesh, William B.; Baylis, Matthew; Goldberg, Tony; Slingenbergh, Jan; Gale, Paul; Venturini, Tommaso; Catchpole, Mike; de Balogh, Katinka; Pautasso, Marco; et al.
Abstract: The history of agriculture includes many animal and plant disease events that have had major consequences for the sector, as well as for humans. At the same time, human activities beyond agriculture have often driven the emergence of diseases. The more that humans expand the footprint of the global population, encroach into natural habitats, alter these habitats to extract resources and intensify food production, as well as move animals, people and commodities along with the pathogens they carry, the greater the potential for pathogens and pests to spread and for infection to emerge or re‐emerge. While essential to human well‐being, producing food also plays a major role in disease dynamics. The risk of emergence of pests and pathogens has increased as a consequence of global changes in the way food is produced, moved and consumed. Climate change is likely to increase pressure on the availability of food and provide newly suitable conditions for invasive pests and pathogens. Human population displacements due to economic, political and humanitarian crises represent another set of potential drivers for emerging issues. The overlapping drivers of plant, animal and human disease emergence and environmental changes point towards the concept of 'One Health'. This paradigm underlines the urgent need to understand the influence of human behaviour and incorporate this understanding into our approach to emerging risks. For this, we face two major challenges. One is cultural; the second is methodological. We have to look at systems not under the narrow view of specific hazards but with a wider approach to system dynamics, and consider a broad spectrum of potential outcomes in terms of risk. In addition, we have to make sense of the vast amounts of data that are available in the modern age. This paper aims to help in preparing for the cultural and methodological shifts needed in our approach to emerging risks.